Hydrogen export competitiveness index for a sustainable hydrogen economy - Dawood Hjeij (17821376) (2023)
The transition to cleaner energy sources, including renewables, introduces the need for versatile and transportable energy carriers such as hydrogen. This paper aims to quantify the hydrogen export competitiveness of all countries using a newly developed comprehensive index. The developed competitiveness index includes 21 indicators under four main categories: resource availability and potential, economic and financial potential, political and regulatory status, and industrial knowledge. Expert interviews and surveys are conducted to properly identify, choose and modify the categories and indicators, and to calculate the appropriate weight for each. Top-ranking countries include the United States, Australia, Canada, United Kingdom, China, Norway, India, Russia, Netherlands, and Germany, and they are poised to be significant players in the hydrogen market. Policy recommendations for growing the hydrogen production and export sector are given based on each category. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2023.05.024